Salários de reinserção no mercado de trabalho brasileiro considerando o Programa Seguro-Desemprego no Brasil - Amorim, Domingos Isaias Maia (2021)
This work provides new estimates of the effect of the Brazilian Unemployment Insurance Program(Programa Seguro-Desemprego)at the national level and disaggregating the dataconsidering urban and rural areas, usingdata from theNational Household Sample Survey (Pesquisa Nacional de Amostra Por Domicílio -PNAD)on individuals forthe year 2015. The methodologyapplied for empirical analysisis theRegression DiscontinuityDesign (RDD), usingaddedcovariates and entropy balancing. Our objective is to analyzeif there is an effect of theunemploymentbenefit on reinsertion wages,and if it there is apositive relationship, based onthe theoretical references of the Human Capital Theory and Job Search models. Among the main results found, theunemployment benefitprogram does notseem toexercise any significant change in the reinsertion wage, except for workers inthe rural environment. It was also found that malesreceive lower reinsertion wagesthan females,and that the Northeast region of Brazilfeaturesthe highestreinsertion wages.